Norms of social state establishment and ways of their implementation in the Constitution of the Republic of Kazakhstan - Aiteke, К.А.; Koshkinbayeva, А.С.; Tleulessova, Б.Т. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
The study is based on an analysis of the provisions of the Constitution of the Republic of Kazakhstan and legislation regulating the social sphere, models of the welfare state, as well as various approaches to its understanding, which confirm the relevance of this issue. The main objective of the article is to theoretically examine the features of the establishment of a welfare state in the Republic of Kazakhstan, its legal essence, and to develop proposals for improving national legislation and its practical implementation. The article reflects the modern development of scientific approaches in the field of constitutional law. Furthermore, it explores the interaction between social national legislation and constitutional law, which is manifested in the emergence of new models of constitutional development both within national societies and beyond. The principle of the welfare state enshrined in a country's Constitution is reflected not only in defining the goals and objectives of such a state but also in granting it the necessary powers and competencies. The main part of the article examines the concept, features, and legal essence of the welfare state using scientific methods of universal and comparative legal analysis, as well as analyzing theoretical concepts presented in legal literature. In conclusion, the authors identify the key characteristics and distinctive features of the welfare state and provide their recommendations on the legal aspects of its establishment and implementation.